BATIK TRAINING ON NURSING HOUSE ‘WANITA UTAMA’ SURAKARTA - Asri Laksmi Riani; Sarah Rum Handayani; Rahmawati Rahmawati (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2011)
The purpose of this study is to be able to guide and direct the prostitutes (WTS) in Surakarta and it’s surrounding environment on the nursing house